2015
DOI: 10.1016/j.jsps.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing community pharmacist decision to dispense generic or branded medicines; Eastern Province, Alahsa, Saudi Arabia

Abstract: Physical appearance of the consumer is revealed to be one of the main factors affecting the pharmacist decision to dispense generic or branded medicine. Pharmacists practising in hospital affiliated pharmacies were found to be influenced by physicians' recommendation, and prefer to dispense good quality medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Similarly, another study that evaluated physicians' knowledge, perception, and attitude toward generic medicines in Riyadh, Saudi Arabia suggested that lack of knowledge about generic medicines among the prescribers was one of the major factors that were responsible for the low rate of generic medicine prescribing [17]. In a previous qualitative study conducted in Alahsa city (Eastern province), community pharmacists expressed concerns about the quality of generic medicines [18] To the best of our knowledge, there has been no quantitative study using a structured questionnaire and systematic sampling technique has assessed community pharmacists' knowledge and practices towards generic substitution in Saudi Arabia despite the fact that community pharmacists are 'central' in generic medicines substitution. Therefore, the aim of this study is to evaluate community pharmacists' knowledge, perceptions and opinions towards generic medicines and generic substitution, and to assess their current substitution practices.…”
Section: Saudi Healthcare System and Generic Medicines Usementioning
confidence: 99%
“…Similarly, another study that evaluated physicians' knowledge, perception, and attitude toward generic medicines in Riyadh, Saudi Arabia suggested that lack of knowledge about generic medicines among the prescribers was one of the major factors that were responsible for the low rate of generic medicine prescribing [17]. In a previous qualitative study conducted in Alahsa city (Eastern province), community pharmacists expressed concerns about the quality of generic medicines [18] To the best of our knowledge, there has been no quantitative study using a structured questionnaire and systematic sampling technique has assessed community pharmacists' knowledge and practices towards generic substitution in Saudi Arabia despite the fact that community pharmacists are 'central' in generic medicines substitution. Therefore, the aim of this study is to evaluate community pharmacists' knowledge, perceptions and opinions towards generic medicines and generic substitution, and to assess their current substitution practices.…”
Section: Saudi Healthcare System and Generic Medicines Usementioning
confidence: 99%
“…On the other hand, community Pharmacies have been known to consider gain over affordability when dispensing medications to patients. 13 We report here that the levels of generic medications served in the community pharmacies where significantly in favour of branded medications. This finding could be a reflection of the society's attitude towards generic medications, as Saudis prefer European or branded med-icines.…”
Section: Discussionmentioning
confidence: 76%
“…According to a recent evidence, hospital pharmacists are generally influenced by physicians' decision on branded medications, only engaging in generic substitutions when drugs prescribed are not available. 13 In a situation where branded medications are prescribed, the pharmacists are under obligation to serve it even if the equivalent generic is in stock. The use of generics allows flexibility in both dispensing and procurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time the pharmacists are in dilemma whether to dispense a generic drug or a well-known branded drug. 40 In this study this issue is one of the frequent dilemmas among the community pharmacists. This can be because of various reasons.…”
Section: Discussionmentioning
confidence: 95%